The impact of exchange rate misalignment on export competitiveness and foreign investment in Malaysia - Noor Zahirah binti Mohd Sidek (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2010)
Exchange rate misalignment is a perennial issue. Defined as the deviation from the equilibrium exchange rate, persistent misalignments due to overvaluation is expected to undermine the competitiveness of a nation and also represents a form of risk. In this study, we embrace the concept of competitiveness from the perspective of exports and foreign investment which essentially divides the study into three major parts. The first part deals with the estimation of the equilibrium exchange rate and misalignments, followed by chapters that focus on the impact of misalignment on exports and foreign investment. Based on the theory of equilibrium exchange rate, this study estimates the equilibrium exchange rate and the resulting misalignments for the Malaysian ringgit (RM) between 1991Q1 to 2008Q3. Results show persistent overvaluation prior to the crisis but minimal misalignments thereafter. It is suggestive that the institution of exchange control in September 1998 has brought the real exchange rate closer towards the equilibrium, albeit with minor fluctuations. The estimated misalignments then serve as a variable in the export model. Results show that misalignments negatively affect exports at both aggregated and disaggregated levels. Our findings also suggest that the effects of misalignments tend to be asymmetric. Finally, the impact of misalignment on foreign investment is examined with results consistently suggesting that misalignments deter foreign investment inflows. The estimated threshold value shows that the negative effect is only significant when misalignment goes beyond 15 percent level. Hence, exchange rate management is still relevant in promoting competitiveness of both exports and foreign investment in Malaysia.